Optimization of Teacher Working Group (KKG) in Improving PAI Teacher Literacy in Compiling HOTS Questions in Elementary Schools Simeulue Tengah District - Agustina, Restika; Silahuddin, Silahuddin; Zulfatmi, Zulfatmi; Mahfud, Aris; Maulidia, Maulidia; Amri, Hasanul (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
The ability to develop Higher Order Thinking Skills (HOTS) questions is a critical competency emphasized in the Merdeka Curriculum, particularly in Islamic Religious Education (PAI) at the elementary level. However, the literacy of PAI teachers in designing HOTS questions remains low in the Simeulue Tengah District. This study aims to assess PAI teachers' literacy in formulating HOTS questions, their participation in Teacher Working Groups (KKG), and the main barriers to effective KKG utilization. A descriptive qualitative approach was employed, using both open- and close-ended questionnaires distributed to 12 PAI teachers from 10 elementary schools. Data were analyzed using descriptive statistics. The findings indicate that although 66.7% of teachers found the KKG beneficial for developing HOTS questions, participation levels were low: 58% rarely attended KKG activities, and only 25% felt significantly supported. The main barriers identified include time constraints due to workload and household responsibilities, minimal support from principals and supervisors, limited access to resources such as digital media and contextual teaching materials, low teacher awareness of the benefits of KKG, and training sessions that are often too theoretical and lack contextual relevance. To optimize the effectiveness of KKG, training must be more practical and context-based, with sustained pedagogical discussions and stronger institutional support. Strengthening the role of KKG is essential for enhancing PAI teachers’ capacity to develop HOTS questions and, ultimately, to improve the quality of religious education.